2009
DOI: 10.2174/138920109788922083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antibiotics and Antimicrobial Peptides on Single Protein Motility

Abstract: Following the movement of individual molecules of a bacterial surface protein in vivo we investigated the effects of antibiotics and antimicrobial peptides on protein motility and membrane structure. In previous work we engineered the lambda-receptor of Escherichia coli such that less than one receptor per cell is in vivo biotinylated and can bind to a streptavidin coated bead. Such a bead served as a handle for the optical tweezers to follow the motion of an individual receptor. In an un-perturbed living cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The motion of the lambda receptor was shown to be diffusive, with a larger diffusion constant than typically observed for protein motion in eukaryotic membranes, meanwhile having an elastic response due to cell wall tethering . Interestingly, the motion was shown to be strongly dependent on the bacterial metabolism (i.e., the motion contained an active component which required a fully functional metabolism).…”
Section: Observed Dynamics Of Organelles and Single Molecules In Vivomentioning
confidence: 99%
“…The motion of the lambda receptor was shown to be diffusive, with a larger diffusion constant than typically observed for protein motion in eukaryotic membranes, meanwhile having an elastic response due to cell wall tethering . Interestingly, the motion was shown to be strongly dependent on the bacterial metabolism (i.e., the motion contained an active component which required a fully functional metabolism).…”
Section: Observed Dynamics Of Organelles and Single Molecules In Vivomentioning
confidence: 99%
“…Also, the dynamics of the l-receptor was found to be energy dependent 81 and to correlate with the dynamic reassembly of the peptidoglycan layer. 82 These findings indicated that the l-receptor is attached to the peptidoglycan layer and that its diffusion is closely linked to the metabolism of the cell, hence it is not a pure thermal diffusion. These results suggest that membrane diffusion studied in vitro will be different from in vivo studies as the active component linked to cell metabolism is lacking in vitro.…”
Section: Membrane Protein Dynamicsmentioning
confidence: 94%
“…4b), was shown to be connected more tightly to the membrane than typical eukaryotic membrane proteins and to have a higher diffusion constant 37,48 . Interestingly, the diffusion of the l-receptor is dependent on the bacterial metabolism of the host cell: if the cell is depleted of energy, the proteins move significantly less 14,49 . Figure 4c shows a time series of the positions visited by a particular l-receptor both before and after poisoning the cell with azide and arsenate to effectively stop electron transport and ATP synthesis.…”
Section: Getting a Handle On The Biological Systemmentioning
confidence: 99%